(untitled) (Research, Society and Development, 2021)
The vegetables intercropping practice triumph in family farming depends on several production factors, including the crops involved, green manuring and plant density of component crops. Therefore, the aim of this work was to assess whether there is agro-economic viability in the radish-arugula intercropping, in different equitable amounts of M. aegyptia and C. procera biomass (20, 35, 50 and 65 t ha-1 on base dry) and in diverse arugula population densities (40, 60, 80 and 100% of that recommended density for single crop - RDSC), combined with 100% of the RDSC for radish in two cropping years. The characteristics, the commercial productivity of radish roots and the arugula green mass yield were evaluated and in the intercropped system, the agronomic indices: land equivalent ratio (LER), intercropping advantage (IA), actual yield loss (AYL), productive efficiency index (PEI), score of the canonical variable (Z), and the economic indicators: gross income (GI), net income (NI), rate of return (RR) and profit margin (PM). The greatest agro-economic advantages of the radish-arugula intercropping were achieved with an LER of 1.64, PEI of 0.86, Z of 1.54, GI of R 45,543.92 ha-1, NI of R 24,662,31 ha-1, RR of R 2.20 for each real invested, and PM of 56.37%, respectively, in the combination of 65 t ha-1 of M. aegyptia and C. procera biomass and arugula population density of 100% of the RDSC, corresponding to the density of 1 million plants per hectare.